Peningkatan Pengetahuan Santriwati dalam Rangka Implementasi PHBS Untuk Mencegah Timbulnya Penyakit di Ponpes Aisyah - Rusmayadi Rusmayadi; Hamidatun Rabayya Yusuf; Rafi’ah Rafi’ah (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
Clean and Healthy Living Behavior (PHBS) is one of the important pillars in efforts to prevent disease and improve public health. In the pesantren environment, especially among female santri, knowledge and application of PHBS are very crucial to prevent the onset of various diseases, both infectious and non-communicable. To increase public knowledge, health education is needed with the right media so that it is easily understood so that it affects changes in knowledge and attitudes. The purpose of this community service activity is to increase santriwati's understanding of the importance of implementing PHBS in the surrounding environment. The service is carried out from preparation to evaluation. The methods used in the service are health education lecture methods, direct application in the field as well as brainstroming, and interactive question and answer. This service activity involved 80 female students at Ponpes Aisyah Sumbawa. PHBS counseling activities went smoothly, all students enthusiastically participated in this PKM activity. Based on the results of observations, this PKM activity was able to increase students' awareness and knowledge in order to practice Clean and Healthy Living behavior.